The Problem of Poverty and the Assessment of its Level in Modern Conditions - Nargiza, Kamilova (European Journal of Life Safety and Stability (2660-9630), 2022)
The problem of poverty has been worrying human society for a long time. But, despite this, humanity has not been able to solve this problem. And, paradoxically, poverty continues to be an inherent feature of any society. Poverty is multidimensional in nature and causes. It cannot be defeated by increasing benefits, creating jobs, providing access to credit for starting a business, or improving housing conditions.